Graduating student nurses' and student podiatrists' wound care competence - An integrative literature review - Emilia Kielo; Leena Salminen; Minna Stolt (My University, 2022)
The objective of this literature review is to describe graduating student nurses' and student podiatrists' wound care competence. This integrative literature review has been conducted with a systematic search process. Original studies were analysed by qualitative content analysis with the following stages: open coding, creating categories and abstraction. The literature search was conducted on May 2016 and reconducted on October 2016 using the Medline/Pubmed, CINAHL, Cochrane Library, Web of Science, Scopus and National Medic databases and 12 original studies were found. All the studies addressed graduating student nurses' wound care competence. According to original studies, graduating student nurses' wound care competence was inadequate. However, the students showed a positive attitude towards wound care. Subthemes of this literature review were: 1) Wound care knowledge, 2) Attitudes towards wound care, 3) Wound care preparedness and 4) Wound care education which created the main theme Graduating nurses' wound care competence. No studies were found about graduating student podiatrists' wound care competence. Graduating student nurses' wound care knowledge was deficient. Wound care education seemed to have a positive relation to students' wound care competence. The findings indicate that more information about graduating student nurses', and especially graduating podiatrists', wound care competence is needed.